Unit two - Key concepts: assessment and management from basin to user. [Training/Course material] - Fraiture, Charlotte de; David, S.; Smith, L.; Varma, Samyuktha (2009)
This unit is concerned with key concepts of assessment and management at scales from the water user to the river basin. The first section outlines the various scales of assessment of water resources and discusses the relationship between the various scales. Section 2 focuses in on the river basin scale and presents a number of key tools for understanding and assessing water resources at this scale. This section describes development trajectories of river basins and provides an overview of key issues which affect river basins. Section 3 introduces the new and prevalent water management paradigm of river basin management. Challenges and a general critique are provided in this section and a typology of river basin management models is presented. Section 4 focuses on Integrated Water Resources Management (IWRM); reviewing the evolution of the concept of integrated approaches, providing a description of IWRM and a definition, and evaluating critically the concept as an operational approach.